New perspectives on an iconic landscape from comparative international long‐term ecological research. Issue 10 (22nd October 2015) - Gaiser, Evelyn E.; Anderson, Elizabeth P.; Castañeda-Moya, Edward; Collado-Vides, Ligia; Fourqurean, James W.; Heithaus, Michael R.; Jaffé, Rudolf; Lagomasino, David; Oehm, Nicholas J.; Price, René M.; Rivera-Monroy, Victor H.; Chowdhury, Rinku Roy; et al.
Abstract : Iconic ecosystems like the Florida Coastal Everglades can serve as sentinels of environmental change from local to global scales. This characteristic can help inform general theory about how and why ecosystems transform, particularly if distinctive ecosystem properties are studied over long time scales and compared to those of similar ecosystems elsewhere. Here we review the ways in which long‐term, comparative, international research has provided perspectives on iconic features of the Everglades that have, in turn, informed general ecosystem paradigms. Studies in other comparable wetlands from the Caribbean to Australia have shed light on distinctive and puzzling aspects such as the "upside‐down estuary" and "productivity paradox" for which the Everglades is known. These studies suggest that coastal wetlands on carbonate (karstic) platforms have: (1) hydrological and biogeochemical properties that reflect "hidden" groundwater sources of water and nutrients, (2) very productive, mat‐forming algal communities that present a low‐quality food to aquatic consumers that encourages (3) highly diversified feeding strategies within and among populations, and (4) extensive and productive seagrass meadows and mangrove forests that promote strong cultural dependencies associated with the ecosystem services they provide. The contribution of international research to each of these general ecological topics is discussed with a particular goal of encouraging informed decision‐making in threatened wetlands across the globe.